Presence of Demodex bovis in bovine feces- Case Report (Veterinária Notícias, 2013)
This paper reports a finding of Demodex bovis in cattle feces in Brazil. A calf of about six months old, from a dairy establishment of the municipality of Paty do Alferes, Rio de Janeiro State had their stools examined by parasitological methods for the investigation of intestinal parasites. This fact suggests that the calf has ingested the mite during breastfeeding, having gone to the parasite's digestive system and mixed with the stool.